El ano de nuestra revolucion : cuentos y poemas - Cofer, Judith Ortiz, 1952-; Olazagasti-Segovia, Elena (Houston, Tex. : Pinata Books, 2006)
A collection of poems, short stories, and essays address the theme of straddling two cultures as do the offspring of Hispanic parents living in the United States.
Spanish translation of Year of our revolution.
Keywords: Hispanic Americans -- Literary collections; Spanish language materials